Benefits of Honey Extract Againt Wound Healing - Bobi Wijaya (HM Publisher, 2022)
The use of honey in wound care was widely used since ancient times. Honey bee shown to have antibacterial properties, and low pH levels create environmental conditions and are not supportive for bacterial growth. Clinical observations from human trials report that honey helps granulated tissue formation, increases epithelization, and reduces inflammation, which affects the acceleration of wound healing. The purpose of this study is to find out the effect of honey on wound healing. Research takes the form of literature review. Literature is taken from one database, PubMed. The key word used is honey and wound healing. and selected with the criteria of inclusion and exclusion obtained ten literature to be reviewed. Honey gives good results and affects the healing of skin wounds, among which there are several types of honey studied in experimental animals and in trying people. In conclusion, honey has an influence on the healing of skin wounds.